(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this article, we manage iterative methods for approximation of fixed points and their applications. We initially talk about fixed point theorems for a non-expansive mapping or a group of non-expansive mappings. Specifically, we express a fixed point hypothesis which addressed certifiably a problem posed during the Conference on Fixed Point Theory. We manage weak and strong union theorems of Mann’s compose and Halpern’s write in a Banach space. At last, utilizing these results, we consider the plausibility problem by raised blends of non-expansive withdrawals and the curved minimization problem of finding a minimizer of an arched function.